Deoxynivalenol and its modified forms: key enzymes, inter-individual and interspecies differences in metabolism. (3rd July 2022) - Wang, Yating; Li, Jiefeng; Wang, Xu; Wu, Wenda; Nepovimova, Eugenie; Wu, Qinghua; Kuca, Kamil
Abstract: Deoxynivalenol (DON) and its modified forms, including DON-3-glucoside (DON-3G), pose a major agricultural and food safety issue in the world. Their metabolites are relatively well-characterized; however, their metabolizing enzymes have not been fully explored. UDP-glucuronosyltransferases, 3- O -acetyltransferase, and glutathione S -transferase are involved in the formation of DON-glucuronides, 3-acetyl-DON, and DON-glutathione, respectively. There are interindividual differences in the metabolism of these toxins, including variation with respect to sex. Furthermore, interspecies differences in DON metabolism have been revealed, including differences in the major metabolites of DON, the role of de-acetylation, and the hydrolysis of DON-3G. In this review, we summarized the major enzymes involved in metabolizing DON to its modified forms, focusing on the differences in metabolism of DON and its modified forms between individuals and species. This work provides important insight into the toxicity of DON and its derivatives in humans and animals, and provides scientific basis for the development of safer and more efficient biological detoxification methods.